Estudio de la técnica de autoensamblado capa por capa de nanopartículas de plata en soportes carbonosos y su evaluación como sensores para la detección de cianuro - Cárdenas Riojas, Andy Alfredo (2018)
The use of metallic nanoparticles in sensors is due to the characteristic properties of these materials at the nano scale, principally the increase in surface area. The surface area decreases when the nanoparticles agglomerate, with the need to support them in substrates with a high surface area. In this research work the self-assembly layer by layer method is studied to anchor silver nanoparticles in different carbons surfaces: hierarchical porous carbons, carbon nanotubes with different functionalities (Without functionalizing, functionalized with -COOH and -OH) and the effect is evaluated on the detection of free cyanide. The silver nanoparticles have been synthesized using two different reducing agents (sodium citrate and tyrosine). The characterization of the nanoparticles by cyclic voltammetry in acidic medium showed a characteristic peak of striping at 0,4 V; by Dynamic Light Dispersion an average diameter of 42,6 nm was obtained for sodium citrate and 57,6 nm for tyrosine, by UV-visible the surface plasmon resonance at 400 nm characteristic of silver nanoparticles was observed. The hierarchical porous carbons (HPC) were synthesized from rigid molds of SiO2 nanoparticles of different sizes, obtaining carbons with different pore size. The HPC was compared with commercial carbon nanotubes, (MWCNT, MWCNT-OH and MWCNT-COOH). The electroactive area of each carbons material was determined by capacitance measurements at low scanning speeds, results that were contrasted with the BET area. The study of the self-assembled layer by layer technique was performed using the silver nanoparticles with tyrosine for their stability during the measurements, being more stable the sensors based on multi-walled nanotubes without functionalizing (NpAg-Tyr-MWCNT) and in porous carbons nested 400 nm in diameter (NpAg-Tyr-HPC-400 nm), results that were corroborated by cyclic voltammetry in basic medium where the presence of silver was observed after assembly. Finally, these sensors NpAg-Tyr-MWCNT and NpAg-Tyr-HPC-400 nm were evaluated against the detection of free cyanide by potentiometry. The NpAg-Tyr-MWCNT sensor presented a limit of detection 2,03 µg L-1. The NpAg-Tyr-HPC-400 nm sensor presented a limit of detection 1,75 µg L-1. Interfering studies at concentrations less than 1 ppm of the interfering ion do not vary the selectivity of the sensors.